Prospects and challenges of selectivity proteinuria index in clinical practices - Qi-liang Chen; Bing Dai (Linchuang shenzangbing zazhi)
Plasma proteins are selectively filtrated by glomerular filtration membrane due to their sizes and charge barriers. By comparing renal clearance of a larger molecular weight to a smaller molecular weight protein in plasma, selectivity proteinuria index (SPI) reflects the severity of injury in glomerular filtration membrane as well as the change of overall glomerular permeability in active nephrons. SPI is not only a convenient marker for patients with contraindications to renal biopsy and may be applied in areas where renal biopsy technique is not available, but also makes up for defects of focal renal biopsy tissues. Kidney Disease: Improving Global Outcomes (KDIGO) Guideline for Membranous Nephropathy has proposed SPI as one of the clinical indicators for risk stratification, initiation and decision on therapeutic strategies. However, SPI also has such limitations as inconsistent formulae, suboptimal specificity and complicated interfering factors. It is of great significance to guide clinical practices along with other indicators. This review summarized the basic principles, calculation methods, clinical application values and challenges of SPI.